2006
DOI: 10.1001/archpsyc.63.7.824
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Obesity and Psychiatric Disorders in the US Adult Population

Abstract: Obesity is associated with an approximately 25% increase in odds of mood and anxiety disorders and an approximately 25% decrease in odds of substance use disorders. Variation across demographic groups suggests that social or cultural factors may moderate or mediate the association between obesity and mood disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

65
807
14
46

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,130 publications
(963 citation statements)
references
References 63 publications
65
807
14
46
Order By: Relevance
“…Reciprocal relations among anxiety, distress, strain, depression and sleep disturbances have been suggested earlier [4,6,30,56]. These psychological symptoms are closely linked to obesity, smoking and physical inactivity [14,17,22,35,43,51,53], which have been suggested as risk factors for neck, shoulder and low back pains in adolescence [5,25,31,32,42]. Our findings that insufficient quantity or quality of sleep increases the risk of neck and low back pains independently of depressive mood, physical activity, sedentary behavior, smoking, BMI and parents' socioeconomic status may indicate that it has a mediating effect, explaining the relationship between social pressures, psychological symptoms and musculoskeletal pains.…”
Section: Discussionmentioning
confidence: 69%
“…Reciprocal relations among anxiety, distress, strain, depression and sleep disturbances have been suggested earlier [4,6,30,56]. These psychological symptoms are closely linked to obesity, smoking and physical inactivity [14,17,22,35,43,51,53], which have been suggested as risk factors for neck, shoulder and low back pains in adolescence [5,25,31,32,42]. Our findings that insufficient quantity or quality of sleep increases the risk of neck and low back pains independently of depressive mood, physical activity, sedentary behavior, smoking, BMI and parents' socioeconomic status may indicate that it has a mediating effect, explaining the relationship between social pressures, psychological symptoms and musculoskeletal pains.…”
Section: Discussionmentioning
confidence: 69%
“…However, research in adults can also throw light upon this unexpected finding. In a community sample of adults, Simon et al [36] recently demonstrated a stronger association of obesity and mental disorders in individuals with higher educational attainment. This high SES group was also among those with the lowest overall rates of obesity.…”
Section: Discussionmentioning
confidence: 98%
“…This high SES group was also among those with the lowest overall rates of obesity. Simon and colleagues [36] hypothesize that the social discrimination of overweight individuals has a stronger impact in socio-demographic groups with lower obesity rates. In line with our Ôspirit of the times hypothesis', we also assume that the mere presence of obesity might be most stressful in high SES groups.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the above hypothesis that leptin insufficiency contributes to depression, epidemiologic and clinical studies suggest a link between obesity, which is commonly characterized by high, not low, levels of leptin, and depression [27][28][29][30]. It has been reported that obese people are approximately 20% more likely to have depressive disorders than non-obese subjects [29]. The high leptin levels associated with obesity are thought to be caused by leptin resistance, much as type 2 diabetic patients are resistant to insulin.…”
Section: Human Studiesmentioning
confidence: 97%